GAMBARAN HISTOLOGI AORTA TIKUS WISTAR DENGAN DIET LEMAK BABI SETELAH PEMBERIAN EKSTRAK DAUN SIRSAK (annona muricata L.) - Maramis, Reinaldo; Kaseke, Marie; Tanudjadja, G. N. (Universitas Sam Ratulangi, 2014)
Abstract: Soursop leaves contain several antioxidants e.g. flavonoid, vitamin C which have antiatherogenic effect that may inhibit the progression of atherosclerotic lession. The risk factor for atherosclerosis is the consumption of food containing highly saturated fatty acids e.g. lard. Low density Lipoproteins (LDL) will be accumulated within the intima and then be oxidized (LDL-ox). This substances ingested by macrophages, resulting in foam-cell formation. The aim of this study is to find out the histological feature of the aorta of wistar rats having lard diets without the addition of soursop leaf extract; having lard diets along with soursop leaf extract; and with which having lard diets followed by soursop extract. This study used experimental method study consisted of 16 wistar rats dividing into 4 groups: group I without treatment (negative control group), group II using lard diet for 14 days (positive control group), group III using lard diet diet with soursop leaf extract for 14 days (treatment group I), and group IV using lard diet for 14 days, and then followed by soursop leaf extract for 14 days (treatment group II). It was found that the aorta of group I showed foam cells in intima and media layers; in the group II showed foam cells in intima and media layers; group III and IV there were not foam cell in their intima and media layers. Summary: the aorta histological features of wistar rats being given lard diets for 14 days, showed foam cells in intima and media layers. Soursop leaf extract adding to lard diets had effect on decreasing foam cells formation (having protective effect), and the effect of giving lard diets following the addition soursop leaf extract showed a reduction of foam cells formation (having therapeutic effect). Keywords: soursop leaf, lard dietary, foam cell, wistar rat. Â Â Daun sirsak mengandung antioksidan (flavonoid, vitamin C) yang berefek anti-aterogenik, sehingga membuat daun sirsak berkhasiat untuk menghambat perkembangan lesi aterosklerosis. Faktor resiko penyebab aterosklerosis adalah mengonsumsi makanan yang mengandung asam lemak jenuh yang tinggi, antara lain lemak babi. Konsumsi lemak jenuh berlebih dapat mengganggu fungsi sel endotel, sehingga lipoprotein berdensitas rendah (LDL) dapat masuk dan menjadi LDL teroksidasi (LDL-oks). Makrofag menangkap LDL-oks dan menjadi sel busa (lesi dini aterosklerosis). Penelitian ini bertujuan untuk mengetahui gambaran histologi aorta tikus wistar dengan diet lemak babi tanpa pemberian ekstrak daun sirsak, diet lemak babi bersamaan dengan pemberian ekstrak daun sirsak, dan setelah diet lemak babi dilanjutkan pemberian ekstrak daun sirsak. Penelitian bersifat eksperimental. Subjek penelitian terdiri dari 16 ekor tikus wistar yang dibagi menjadi empat kelompok: kelompok I tanpa perlakuan (kelompok kontrol negatif); kelompok II dengan diet lemak babi selama 14 hari (kelompok kontrol positif); kelompok III dengan diet lemak babi serta pemberian ekstrak daun sirsak selama 14 hari (kelompok perlakuan I); kelompok IV dengan diet lemak babi selama 14 hari, dilanjutkan pemberian ekstrak daun sirsak selama 14 hari (kelompok perlakuan II). Hasil penelitian memperlihatkan gambaran histologi aorta tikus wistar kelompok I tampak sel-sel busa pada lapisan intima dan media; pada kelompok II terdapat sel-sel busa; pada kelompok III dan IV tidak terdapat sel busa. Simpulan: tikus wistar dengan diet lemak babi selama 14 hari memperlihatkan gambaran histologi aorta tikus wistar terdapat sel busa pada tunika intima dan tunika media. Pemberian ekstrak daun sirsak bersamaan dengan diet lemak babi berefek menurunkan jumlah sel busaÂ (efek protektif). Pemberian ekstrak daun sirsak setelah diet lemak babi selama 14 hari berefek mengurangi jumlah sel-sel busa yang terbentuk (efek terapi). Kata kunci: daun sirsak, diet lemak babi, tikus wistar.